Adapting a club-based medication delivery strategy to a hypertension context: the CLUBMEDS Study in Nigeria. Issue 7 (9th July 2019) - Santo, Karla; Isiguzo, Godsent C; Atkins, Emily; Mishra, Shiva R; Panda, Rajmohan; Mbau, Lilian; Fayomi, Samuel B; Ugwu, Collins; Odili, Augustine; Virani, Salim
Abstract : Introduction: The prevalence of hypertension in sub-Saharan Africa is among the world's highest; however, awareness, treatment and control of hypertension in this region are suboptimal. Among other barriers, the overburdened healthcare system poses a great challenge for hypertension control. Community peer-support groups are an alternative and promising strategy to improve adherence and blood pressure (BP) control. The CLUBMEDS study aims to evaluate the feasibility and impact of adherence clubs to improve hypertension control in Nigeria. Methods and analysis: The CLUBMEDS study will include a formative (pre-implementation) qualitative evaluation, a pilot study and a process (postimplementation) qualitative evaluation. At the formative stages, focus group discussions with patient groups and in-depth interviews with healthcare providers, managers and key decision makers will be conducted to understand the feasibility, barriers and facilitators, opportunities and challenges for the successful implementation of the CLUBMEDS strategy. The CLUBMEDS pilot study will be implemented in two primary healthcare facilities, one urban and one rural, in Southeast Nigeria. Each adherence club, which consists of a group of 10–15 patients with hypertension under the leadership of a role-model patient, serves as a support group to encourage and facilitate adherence, BP self-monitoring and medication delivery on a monthly basis. A process evaluation will be conducted at the end of the pilot study to evaluate the acceptability and engagement with the CLUBMEDS strategy. To date, 104 patients were recruited and grouped into nine clubs, in which patients will be followed-up for 6 months. Ethics and dissemination: The study was approved by the University of Abuja Teaching Hospital and the Federal Teaching Hospital Abakaliki Human Research Ethics Committees and all patients provided informed consent. Our findings will provide preliminary data on the potential effectiveness and acceptance of this strategy in a hypertension context. Study findings will be disseminated via scientific forums.